KNOWLEDGE, ATTITUDE AND PRACTICES TOWARDS EXCLUSIVE BREASTFEEDING AMONG PRIMIPARA MOTHERS AT LUGASA HEALTH CENTER III KAYUNGA DISTRICT; A DESCRIPTIVE CROSS SECTIONAL STUDY. - KABWIRE, BUSHIRAH; KANSIIME, DAVID (Student's Journal of Health Research Africa, 2024)
Introduction: The main purpose of this study was to determine the knowledge, attitude, and practices towards exclusive breastfeeding among primiPara mothers at Lugasa Health Center iii, Kayunga district; the study focused mainly on three objectives that are to determine the knowledge, to determine the attitude and to assess the practices towards EBF among primiPara mothers. Method: A hospital-based descriptive cross-sectional study was conducted between March 2023 and April, 2023 at Lugasa health center iii in Kayunga District. Data was collected using questionnaires and a simple random sampling technique was employed to select 130 study participants. Data was analyzed using Microsoft Excel and a scientific calculator. Results: Data analysis and interpretation showed that 61.5% of the respondents defined EFB as feeding babies on breast milk only, 91.5%, knew breast milk as the cheapest and recommended food for the newly born baby, 48.5% knew that babies should be breastfed on breast milk only for the first six months of life 60% of respondents knew that a baby should be breastfed eight times and more in a day and 76% knew that EFB decreases childhood diseases and death. The study results reflected that 68.5% of the study respondents perceived the act of EBF as an easy process, and 49% reported the act of breastfeeding in public also to be okay. Conclusion: The majority of the study respondents had satisfactory knowledge, favorable attitudes, and good practices towards EBF. However, the practice of EBF in the study area is still lower than the set national target of the prevalence of EBF and the WHO set global prevalence of EBF. Recommendations: The study recommends combined efforts from different stakeholders like the government, Ministry of Health, District Health Teams, and health workers to promote appropriate Infant and young child Feeding Practices like EBF in the country.